2018
DOI: 10.12659/aot.910176
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Hepatitis B Infection in Liver Transplant Patients Receiving Long-Term Hepatitis B Immunoglobulin Prophylaxis

Abstract: BackgroundLong-term real-world data are relatively sparse regarding recurrence of chronic hepatitis B virus (HBV) infection after liver transplantation using hepatitis B immunoglobulin (HBIg) and nucleos(t)ide analogue (NUC) prophylaxis.Material/MethodsData from 371 adults transplanted for HBV-related disease at 20 European centers and given HBIg for ≥12 months ± NUC therapy were analyzed retrospectively.ResultsHBIg comprised Hepatect® (iv HBIgB; n=299), subcutaneous Zutectra® (sc HBIg, n=236), and other HBIg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
3
19
1
Order By: Relevance
“…To assess the specificity of our viral internalization assay we evaluated the effect of known HBV entry inhibitors: heparin that competes for virus attachment to cellular HSPGs 10 ; MyrB 30 and Hepatect a polyclonal anti-HBV Ig that neutralizes viral infection 31 . All of the entry inhibitors were used at a concentration that neutralized >90% of HBV infection (judged by HBeAg expression at 5d post-infection) and significantly reduced intracellular HBV DNA levels by more than 80% after 6h post inoculation ( Fig.3b ).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the specificity of our viral internalization assay we evaluated the effect of known HBV entry inhibitors: heparin that competes for virus attachment to cellular HSPGs 10 ; MyrB 30 and Hepatect a polyclonal anti-HBV Ig that neutralizes viral infection 31 . All of the entry inhibitors were used at a concentration that neutralized >90% of HBV infection (judged by HBeAg expression at 5d post-infection) and significantly reduced intracellular HBV DNA levels by more than 80% after 6h post inoculation ( Fig.3b ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, a Chinese registry indicated that low‐dose IM HBIG in combination with a NA (mainly ETV) was an effective prophylactic option against HBV recurrence 54 . In the same concept, the efficacy of SC HBIG has been evaluated in a recent European multicentre retrospective study of 371 patients who received long‐term routine prophylaxis with IV or SC HBIG for a minimum of 1 year in combination with LAM or a newer NA 39 . Of the 16 patients who experienced HBV recurrence, 11 were receiving HBIG at the time of recurrence, but only one patient was under SC HBIG, with anti‐HBs levels <100 IU/L 39 .…”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 99%
“…In the same concept, the efficacy of SC HBIG has been evaluated in a recent European multicentre retrospective study of 371 patients who received long‐term routine prophylaxis with IV or SC HBIG for a minimum of 1 year in combination with LAM or a newer NA 39 . Of the 16 patients who experienced HBV recurrence, 11 were receiving HBIG at the time of recurrence, but only one patient was under SC HBIG, with anti‐HBs levels <100 IU/L 39 . Another multicentre study evidenced that the early introduction of SC HBIG by week 3 after LT, in combination with NA, effectively prevented HBV recurrence, with no treatment failures reported 38 .…”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 99%
“…56 In these cases, prophylaxis with HBV immunoglobulin is recommended. 57 However, data from several meta-analyses have revealed the benefits of adding lamivudine to the HBV immunoglobulin with regard to HBV, HCC recurrence and survival rates. [58][59][60] Nevertheless, adding adefovir to the HBV immunoglobulin was found to be superior to lamivudine plus HBV immunoglobulin.…”
Section: Prediction Of Hcc After Treatment With Nucleos(t) Ide Analoguesmentioning
confidence: 99%